El método Doman para el desarrollo de la inteligencia matemática de los niños del subnivel 2 de Educación Inicial de la Unidad Educativa Yaruquíes, de la cuidad de Riobamba, periodo 2022 - Quera Londo, Sara Abigail (2022)
This research work was carried out based on the scope of the intelligence bits in early childhood education, the general objective was to analyze the importance of the Doman method in the development of mathematical intelligence in children of sublevel 2 of the Yaruquíes Educational Unit. of the city of Riobamba, period 2022. References from previous research that give reliability and relevance to the investigation are presented. In addition, primary and secondary sources of information were analyzed to support the methodology that guided the development of the work, with a mixed approach, non-experimental design and a descriptive type, bibliographic and cross-sectional research, this allowed the elaboration of the instruments to obtain data, such as a questionnaire applied to the teacher to determine the level of knowledge about the Doman method with the development of bits of intelligence, and an observation sheet that was applied in two moments, the first, in a class where the teacher worked with the traditional methodology and the second, after the Doman method was applied, this allowed the analysis of how the development of mathematical intelligence occurs through the use of this method in infants. This study allowed the design of a manual for teachers to apply the Doman method with bits of intelligence in the teaching learning process with children aged from 4 to 5 years old. The results obtained in the investigation are favorable since it was evidenced that the Doman method has a great influence on the development of children's mathematical intelligence.